Kumpulan cerita pendek Australia Geoffrey Dutton; Penyunting, Ismail Marahimin, II,Yudhi Soenarto, dan A. Salam rasjidi; Penerjemah, I Yudhi Soenarto dkk - DUTTON, Geoffrey; MARAHIMIN, Ismail; SUNARTO, I Yudhi; RASJIDI, A.Salam; SOENARTO, I Yudhi dkk (1994)
331 hlm 21 cm